Evaluation of serum levels of interferon beta and nucleotide binding and oligomerization domain 2 gene polymorphism in children with cough asthma phenotype: a case-control study - Magdy M. Zedan; Doaa M. Radwan; Nashwa Khairat Abousamra; Yahya Mohammed Wahba; Engy Osman (SpringerOpen, 2023)
Abstract Background Individuals with asthma are thought to suffer from a variety of distinct disorders, or phenotypes, each of which is characterized by a unique combination of genetic and environmental factors. Syndromes that are exacerbated by allergens, non-allergic factors, and aspirin, as well as syndromes that are best differentiated by pathologic findings, response to therapy, and natural history, fall into this category. The best course of treatment for an individual patient with asthma can be determined by first determining his or her specific asthma phenotype and its underlying pathophysiology. Aim of the work Explore clinical characteristics, serum INF-β in cough asthma phenotype and allergic march asthmatic children. Also, to assess the association of NOD2 (rs2066845) gene polymorphism among those asthma phenotypes in Egyptian asthmatic children. Patients and methods The study included 64 cough phenotypic asthmatic children and 60 allergic march phenotypic asthmatic children in addition to 39 healthy controls (control group). The included children were subjected to full clinical history taking, full clinical examination, assessment of (total serum IgE, CBC for peripheral eosinophil percentage, cytokine profile (serum levels of INF-B), and genetic analysis: SNPs of NOD2 (rs2066845). Results There was a significant increase in G allele frequency, in both homozygous (GG) and heterozygous (GC) states, among asthmatic children of cough and allergic march phenotypes compared to healthy controls, with no significant difference between the two phenotypes. In addition, serum INF-β was significantly lower in cough and allergic march phenotypic asthmatics with GG genotypes versus healthy controls of the same genotype. Conclusions NOD2 (rs2066845) gene polymorphism is associated with both cough and allergic march asthma phenotypes in Egyptian asthmatic children. It was also shown that G allele may be implicated in asthma pathophysiology.